Analisis Hubungan Antara Makro Ekonomi dan Indeks Sektoral di Bursa Efek Indonesia - Dian Surya Sampurna; Syifa Fauziah (Jurnal Ekonomi, 2021)
This study aims to determine the relationship between the rupiah exchange rate, world oil prices, inflation and the selected sectoral indices, namely the mining sector, the financial sector, as well as the basic and chemical industry sectors. This study uses a stationary test, cointegration test, and Granger causality test with Eviews10 software. The population of this research is sectoral index, rupiah exchange rate, inflation and world oil prices. While the samples of this research are the rupiah exchange rate, world oil prices, inflation, the mining sector, the financial sector, and the basic and chemical industry sector for the period January 2017 – March 2021. The data used in this study is secondary data in the form of time series data. Data collection techniques used the documentation method taken in the form of monthly data through the official websites www.idx.co.id, www.bi.go.id, and www.investing.com. The results of this study indicate that the rupiah exchange rate, world oil prices, inflation, the mining sector, the financial sector, as well as the basic and chemical industry sectors are stationary at the first difference level. The results of the Johansen Test show that there is no cointegration between variables in this study. There is a causality between inflation and the mining sector, the basic and chemical industry sector and the rupiah exchange rate as well as a causality between the financial sector, the mining sector, and the basic and chemical industrial sector and world oil prices. Furthermore, the rupiah exchange rate, world oil prices, and inflation have an impact on the mining sector, the financial sector, as well as the basic and chemical industry sectors.